2017
DOI: 10.3389/fpsyg.2017.00495
|View full text |Cite
|
Sign up to set email alerts
|

When Is Humiliation More Intense? The Role of Audience Laughter and Threats to the Self

Abstract: In personal accounts, humiliation is often reported as a very intense, painful, negative emotion. We report two scenario studies in which we explored two factors that may contribute to the intense character of humiliation: (1) unwanted, negative public exposure, and (2) a threat to central aspects of one's identity. Study 1 (N = 115) assessed emotional reactions to a public insult when an audience responded with either laughter or not and when someone from the audience offered support after the insult or no su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Humiliation is often reported as a very concentrated, painful and negative emotion (Mann et al, 2017). Lack of confidence and peer pressure make the students embarrassed, which negatively affects the student's self-esteem Hyvärinen, Sahito, Uusiautti, & Määttä 62 and self-confidence and leads them towards the feelings of inferiority and ignorance, and fade the joy of learning (see also Mujiyati & Adiputra, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Humiliation is often reported as a very concentrated, painful and negative emotion (Mann et al, 2017). Lack of confidence and peer pressure make the students embarrassed, which negatively affects the student's self-esteem Hyvärinen, Sahito, Uusiautti, & Määttä 62 and self-confidence and leads them towards the feelings of inferiority and ignorance, and fade the joy of learning (see also Mujiyati & Adiputra, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is general knowledge about the consequences of some of the attitudes presented here. More specifically, the scientific literature has evidenced how humiliation is a very intense negative emotion that stays in an individual’s memory for longer than other negative emotions, especially when there is an audience who laughs at such an attitude of despisal [ 26 ]. Infidelity to the non-dominant partners was also demonstrated in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also point to the importance of working with men to help them to identify these types of situations and not accept this treatment. In this sense, scientific research has also shown how men with a new alternative masculinity [ 22 ] do not accept double standards and help to overcome the pattern in which some women reproduce the behavior of traditional dominant masculinities [ 26 , 29 ] and only want egalitarian and passionate relationships [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the affect associated with the meaning ascribed to a stimulus can be influenced by contextual factors. Thus, the experience of being challenged or humiliated is likely to be heightened by the presence and reaction of onlookers (Mann 2017). This context may also lead to an aggressive action impulse being favoured since it is associated with an anticipated status boost and/or an avoidance of status loss in comparison with the anticipated outcomes of a non-aggressive response (Anderson 2015).…”
Section: Emotional Processesmentioning
confidence: 99%